Microstructural evolution and high temperature oxidation characteristics of cold sprayed Ni-20Cr nanostructured alloy coating - Swaminathan, Srinivasan; Hong, Sung-Min; Kumar, Manoj; Jung, Woo-Sang; Kim, Dong-Ik; Singh, Harpreet; Choi, In-Suk (ELSEVIER SCIENCE SA, 2019)
Mechanically alloyed Ni-20Cr (wt%) nanocrystalline powder was cold spray deposited on SA 516 Grade 70 steel. The microstructure and high temperature oxidation characteristics of Ni-20Cr nanostructured alloy coated steel have been investigated. The cyclic oxidation was conducted in air at 900 degrees C for periods up to 50 h. The coated steel was examined prior to and after cyclic oxidation using SEM, EDX, FIB, TEM and SAED. The TEM analyses showed that the coating exhibits equiaxed nanoscale microstructure. Interestingly, the high temperature cyclic exposure significantly influences the grain growth despite the segregation and preferential formation of nano islands of Cr2O3 within the coating matrix. Furthermore, the enhanced grain boundary diffusion of Cr in the nanostructured coating promotes the formation of denser Cr-rich protective surface oxide layer, which possesses a superior oxidation resistance, i.e. prevents the corrosion of substrate steel. The microstructural changes, crystallographic and chemical aspects of the Ni-20Cr nanostructured coating upon cyclic exposure are discussed in the context of its high temperature corrosion protection property.
Keywords: FERRITIC STAINLESS-STEELS; CORROSION BEHAVIOR; NI; FE; CU; SUPERALLOYS; PERFORMANCE; ENVIRONMENT; NITRIDATION; TECHNOLOGY